2013
DOI: 10.4271/2013-24-0050
|View full text |Cite
|
Sign up to set email alerts
|

Transient RCCI Operation in a Light-Duty Multi-Cylinder Engine

Abstract: Reactivity Controlled Compression Ignition (RCCI) is an engine combustion strategy that utilizes in-cylinder fuel blending to produce low NO x and PM emissions, while maintaining high thermal efficiency. Previous RCCI steady-state performance studies provided a fundamental understanding of the RCCI combustion process in steady-state, singlecylinder and multi-cylinder engine tests. The current study investigates RCCI and conventional diesel combustion (CDC) operation in a light-duty multi-cylinder engine over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
(35 reference statements)
1
23
0
2
Order By: Relevance
“…A direct comparison is not possible as the OEM results are proprietary and modifications for the Drivven system do not allow the use of the OEM controller. However, these values were found to give similar steady-state emissions results as those from the OEM controller [26]. For RCCI operation, additional tables to control the gasoline PFI system were added.…”
Section: Engine and Controlsmentioning
confidence: 72%
See 1 more Smart Citation
“…A direct comparison is not possible as the OEM results are proprietary and modifications for the Drivven system do not allow the use of the OEM controller. However, these values were found to give similar steady-state emissions results as those from the OEM controller [26]. For RCCI operation, additional tables to control the gasoline PFI system were added.…”
Section: Engine and Controlsmentioning
confidence: 72%
“…First, it is interesting to see how RCCI responds to engine speed changes, but as Glewen showed, an engine speed transient acts similarly to a step-up and then a step-down load transient [26]. Future work should look at load transients as a more fundamental test of transient engine performance.…”
Section: Discussion and Future Workmentioning
confidence: 96%
“…The reactivity controlled compression ignition (RCCI) combustion, initially proposed by Inagaki et al [6] and later developed by Kokjohn et al [7], has been demonstrated to be more promising than previous LTC strategies such us the homogeneous charge compression ignition (HCCI) [8], diesel partially premixed combustion (PPC) [9], gasoline PPC [10] and gasoline PPC spark assisted [11] [12]. The RCCI concept has been extensively studied in different single cylinder engine (SCE) platforms: light- [13], medium- [14] and heavy-duty [15], as well as in multi-cylinder engines [16]. Different strategies have been developed to increase the thermal efficiency of RCCI, such as engine settings optimization: injection settings [17] [18], air management conditions [19]; fuel properties modification: fuel variation [20], use of additives [21], use of biofuels [22]; and hardware optimization: piston bowl geometry modification [23], compression ratio optimization [24] or engine cooling reduction [25].…”
Section: Introductionmentioning
confidence: 99%
“…RCCI combustion is also affected by factors like the wall and the residual gas temperatures [52]. So while going from a lower load to a higher load or vice-versa, these conditions will be different [53].…”
Section: G(s)mentioning
confidence: 99%
“…The main reasons attributed to this were, fuel dynamics [52] and air dynamics [49]. Air dynamics is one of the main factors that caused misfires.…”
Section: Combustion Mode Switchingmentioning
confidence: 99%